Conductive mechanism of reduced lead silicate glass for micro‐channel plate. (26th November 2019) - Huang, Yonggang; Shi, Pan; Zhou, You; Wang, Yun; Fu, Yang; Wang, Jiuwang; Jia, Jinsheng
Abstract: Lead silicate glasses reduced by hydrogen have the characteristics of conductivity like semiconductors and surface secondary electron emission. Therefore, lead silicate glass is the important material of microchannel plate (MCP) for electron multiplier element. The change of bulk resistance (BR) of lead silicate glass (LSG) with hydrogen reducing time and temperature, and hydrogen flow was investigated. The effect of various hydrogen‐reducing parameters on BR is firstly decreasing, then keeping level, and finally increasing. The tendency presents V‐shaped curve. By analyzing the surface composition and morphology of LSG, it is found that the quantity and aggregation state of lead and bismuth are the key factors determining the conductivity of LSG. It is indicated that the electrical conduction is derived from ions and electrons of LSG. The conductive mechanism, however, is different in different stages in the V‐shaped curve. The discovery of V‐shape curve and the conduction mechanism at different stages have important theoretical guiding significance for the fabrication of microchannel plates.